STAGING GENDER THE ROLE OF PERFORMING ARTS IN SOCIALISING REPRODUCTIVE HEALTH AWARENESS - Iqbal, Sadaf; Das, Bithika; Dolly, (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Performing arts folk theatre, street plays, community theatre, dance and participatory performance have long been used to communicate social messages across diverse publics. This paper investigates how performing arts function as sites of gender socialisation and as mechanisms for disseminating reproductive health knowledge. Drawing on a mixed-methods study conducted in urban and semi-urban Indian sites where community theatre interventions were implemented, the research analyses how performances shape gender norms, mediate information about reproductive health, and facilitate dialogic spaces for behavioural change. Findings suggest that when performances are locally grounded, gender-sensitive, and participatory, they can reduce stigma, increase knowledge, and open channels for intergenerational conversation but outcomes are mediated by caste/class, religious norms, and the nature of the art form. The paper concludes with programmatic recommendations for integrating performing arts into public health outreach while safeguarding local agency and sensitivity.